1981
DOI: 10.1042/bj2000441
|View full text |Cite
|
Sign up to set email alerts
|

The selective release of phospholipase A2 by resident mouse peritoneal macrophages

Abstract: Resident mouse peritoneal macrophages have three phospholipase activities: a phospholipase A2 active at pH 4.5, a Ca2+-dependent phospholipase A2 active at pH 8.5 and a phosphatidylinositol-specific phospholipase C activity. When macrophages are exposed to zymosan in culture, the cellular activity of pH-4.5 phospholipase A2 is diminished in a manner dependent on zymosan concentration and time of exposure, whereas the cellular activities of pH-8.5 phospholipase A2 and phospholipase C remain unchanged. The deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…Moskowitz et al (30) demonstrated enhanced phospholipase A2 activity by addition of Mg2+, ATP, and cAMP to brain synaptosomal vesicles. Wightman et al (31) showed a similar activation by ATP in mouse peritoneal macrophage sonicates and further demonstrated that cAMP-dependent protein kinase augmented phospholipase A2 activation. Another possible explanation for the enhanced phospholipase A2 activity with both an increase in [Ca2+] and protein kinase C activity is that the subtype of protein kinase C stimulated by PMA and l-oleoyl 2-diacylglycerol, and hence the substrate specificity, may be altered by the simultaneous increase in cytosolic [Ca2"] (32).…”
Section: Discussionmentioning
confidence: 86%
“…Moskowitz et al (30) demonstrated enhanced phospholipase A2 activity by addition of Mg2+, ATP, and cAMP to brain synaptosomal vesicles. Wightman et al (31) showed a similar activation by ATP in mouse peritoneal macrophage sonicates and further demonstrated that cAMP-dependent protein kinase augmented phospholipase A2 activation. Another possible explanation for the enhanced phospholipase A2 activity with both an increase in [Ca2+] and protein kinase C activity is that the subtype of protein kinase C stimulated by PMA and l-oleoyl 2-diacylglycerol, and hence the substrate specificity, may be altered by the simultaneous increase in cytosolic [Ca2"] (32).…”
Section: Discussionmentioning
confidence: 86%
“…Cyto- solic and secretory PLA2s have been described in a number of cells, including neutrophils (Traynor & Authi, 1981;Balsinde et al, 1988;Ramesha & Ives, 1993), monocytes (Wightman et al, 1981;Ulevitch et al, 1988;Clark et al, 1990) and platelets (Matsumoto et al, 1988;Kramer et al, 1989;Takayama et al, 1991). PLA2 enzymes may be involved in cell proliferation and signal transduction as well as in the pathogenesis of disease processes such as inflammation (Mukherjee et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic treatment of rats with colchicine markedly reduced cell migration and this was accompanied by a significant reduction in PLA2 levels, which confirms that infiltrating neutrophils are the main source of this enzyme activity in the zymosan-injected air pouch exudates. It is interesting to note that zymosan induces in vitro the release of lysosomal enzymes and PLA2 activity in rabbit neutrophils (Traynor & Authi, 1981) and mouse peritoneal macrophages (Wightman et al, 1981).…”
Section: Eicosanoid Levelsmentioning
confidence: 99%
“…Four previously published observations lend credence to this finding. First, an early study reported that peritoneal macrophages secrete a phospolipase A2 activity in response to zymosan characterized by an acidic pH optimum (1). Second, recent studies on the mannose-6-phosphate plasma and urine glycoproteomes reported that LPLA 2 is recovered in both types of biological fluids (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In hematopoietic cells and melanocytes, the lysosomal compartment has dual functions that include degradation and secretion. Almost 30 years ago, macrophages were reported to possess an acid Phospholipase A 2 that was secreted in response to phagocytic stimuli such as zymosan (1). This acidic phospholipase activity released from secretory lysosomes is distinct from that of the small secreted Phospholipase A 2 s (sPLA 2 s).…”
mentioning
confidence: 99%